Hierarchical modeling of blood pressure determinants and outcomes following valsartan treatment in hypertensive patients with known comorbidities: pooled analysis of six prospective real-world studies including 11, 999 patients. (2nd January 2021) - Alkhatib, Nimer; Sun, Diana; Denhaerynck, Kris; Hamarneh, Dina; Van Camp, Yoleen; Villa, Lorenzo; Brié, Heidi; Vancayzeele, Stefaan; MacDonald, Karen; Abraham, Ivo
Abstract: Aims: Six prospective real-world studies of antihypertensive treatment with valsartan-centric regimens were pooled to: (1) examine the effectiveness of ∼90 days of second- or later-line valsartan treatment in hypertensive patients with known comorbidities; and (2) identify physician- and patient-related determinants associated with systolic (SBP) and diastolic blood pressure (DBP) outcomes in these patients. Methods and materials: A pooled analysis was performed of an evaluable sample of 11, 999 hypertensive patients with known comorbidities treated ∼90 days with valsartan-centric regimens. We applied hierarchical linear and logistic regression models to identify determinants of blood pressure (BP) outcomes and a potential physician class effect. Results: Valsartan regimens resulted in mean (SD) SBP and DBP reductions of 18.0 (15.8) mmHg and 9.5 (10.1) mmHg, respectively, at ∼90 days, yielding SBP, DBP and combined SBP/DBP control rates of 44.0%, 67.2% and 39.3%, respectively. About a quarter of the variance in 90 day BP values was attributable to a physician class effect. BP outcomes declined with physicians' increasing years in practice and being male. At the patient level, BP outcomes declined with SBP and DBP at diagnosis; diabetes; higher cholesterol and BMI; lower valsartan and hydrochlorothiazide (HCTZ) doses; and concomitant anti-hypertensives. Older age was associated with improved DBP. A proxy of physician vigilance, cardiovascular disease history, was associated with improved BP outcomes, as were patient adherence and higher doses of valsartan in combination with HCTZ. Conclusions: Valsartan-centric regimens have significant BP lowering benefits in this pooled sample of patients with known comorbidities. Many observed determinants of BP outcomes are modifiable or manageable.